2010
DOI: 10.1177/0020764010387478
|View full text |Cite
|
Sign up to set email alerts
|

Distressed fathers and their children: A review of the literature

Abstract: Most of the quantitative literature focuses on the many risks and negative outcomes for children. However, qualitative studies suggest positive outcomes such as strong parent-child relationships, which demand further attention both in research and in practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Like other research [30], we found that access and custody were major issues for fathers with mental illness, but also discovered eight other areas where men reported parenthood-related experienced discrimination. Our research supports Ackerson’s [21] in finding reports of the stigma of parental mental illness extending to affect children.…”
Section: Discussionsupporting
confidence: 84%
“…Like other research [30], we found that access and custody were major issues for fathers with mental illness, but also discovered eight other areas where men reported parenthood-related experienced discrimination. Our research supports Ackerson’s [21] in finding reports of the stigma of parental mental illness extending to affect children.…”
Section: Discussionsupporting
confidence: 84%
“…The children of men with mental illness are at increased risk of a number of negative psychosocial outcomes, including emotional and behavioural problems (Weitzman, Rosenthal, & Liu, ), psychiatric disorders (Ramchandani et al, ), and poor adolescent adjustment (Ramchandani & Psychogiou, ). (For reviews, see Lefrançois, , and Wilson & Durbin, . )…”
Section: Introductionmentioning
confidence: 99%
“…The children of men with mental illness are at increased risk of a number of negative psychosocial outcomes, including emotional and behavioural problems (Weitzman, Rosenthal, & Liu, 2011), psychiatric disorders (Ramchandani et al, 2008), and poor adolescent adjustment (Ramchandani & Psychogiou, 2009). (For reviews, see Lefrançois, 2012, andWilson &Durbin, 2010. ) There are, however, other bodies of literature that have investigated the relationship between men's mental health and family life, even if the fathering role or children's outcomes are not their central focus.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the active role of children in helping the family deal with difficult situations complements the more common focus on individual coping. This is also evident in the growing body of research focusing on children's roles as carers in families in which parenting by one or both parents is compromised, for example as a result of mental illness (Aldridge, ; LeFrancois, ). In qualitative case studies in five countries, Ungar and others () found that for adolescents who were identified as coping well with chronic adversity, making a contribution to the welfare of their family was advantageous to their own well‐being.…”
Section: Findings and Discussionmentioning
confidence: 99%